(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
This article shows the effectiveness of using active methods of teaching in directing primary school pupils to creative thinking, touched on the possibilities of using "Creative text based on a picture", "Fifth, sixth, seventh...is extra", "Chain word” during lessons. At present, much attention is paid to the issues of scientific research on the problems of language and speech, the features of their connection with culture, which are considered a means of human communication. In connection with the development of society, the mutual exchange of ideas, as well as the rise of culture, directly depend on the characteristics of language and speech. This article explores the linguistic, psycholinguistic features of youth jargon.